MODELING MUSCLE ACTIVITIES OF SQUAT MOTION USING OPENSIM - Julian Harjanto, Samuel
Health is an important thing for humanity in survival. Health is related to the human body which consists of many parts that needs to be maintained, which one of them is the muscle. Muscle health can be assessed from the results of muscle force simulations from the OpenSIM software. OpenSIM is an open-source platform for modeling, simulating, and analyzing the neuromusculoskeletal system. To validate the muscle force simulation results from the OpenSIM software, muscle activity data were collected using surface electromyography. This research step begins with a literature review and the selection of research subjects. After that, the data were collected using sEMG method, optical motion capture, and forceplate from the OpenSIM squat-standing movement model. The data generated from the optical motion capture and forceplate will be used as inputs for the OpenSIM software. The output that can be provided by OpenSIM from those steps is a graph of the working muscle forces. That graph will be compared and analyzed with a graph from the surface electromyography sensor reading results. Based on the results of the analysis conducted, the graph of working muscle forces generated by the OpenSIM software has shown a similar trend to the graph of muscle activity resulting from surface electromyography sensor reading. Therefore, it validated the results from OpenSIM software and implies that the data collecting process has been done precisely. Some suggestions to support further research are assembling wireless sensor devices, using strong adhesives, and learning more about the OpenSIM software.